2007
DOI: 10.1007/s10714-007-0489-0
|View full text |Cite
|
Sign up to set email alerts
|

Concept of temperature in multi-horizon spacetimes: analysis of Schwarzschild–De Sitter metric

Abstract: In case of spacetimes with single horizon, there exist several wellestablished procedures for relating the surface gravity of the horizon to a thermodynamic temperature. Such procedures, however, cannot be extended in a straightforward manner when a spacetime has multiple horizons. In particular, it is not clear whether there exists a notion of global temperature characterizing the multi-horizon spacetimes. We examine the conditions under which a global temperature can exist for a spacetime with two horizons u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 58 publications
(68 reference statements)
4
70
0
Order By: Relevance
“…This result is the same as that of the RN-AdS black hole [38,57,58]. In fact, one can also introduce a "thermally opaque" membrane [45,50,59] between the black hole horizon and the cosmological horizon to construct two different thermal equilibrium states. The two states satisfy Eqs.…”
Section: Discussionsupporting
confidence: 59%
“…This result is the same as that of the RN-AdS black hole [38,57,58]. In fact, one can also introduce a "thermally opaque" membrane [45,50,59] between the black hole horizon and the cosmological horizon to construct two different thermal equilibrium states. The two states satisfy Eqs.…”
Section: Discussionsupporting
confidence: 59%
“…This gave the birth to thermodynamics of black holes [4][5][6]. In 1976 Gibbons and Hawking found that also cosmological horizon emits thermal radiation [7], and this gave rise to thermodynamics of horizons [8][9][10][11][12][13][14][15][16]. The basic point is that an observer for whom a horizon prevents seeing the whole space-time, does not have an access to the complete quantum state of the system, and the loss of information about quantum state is responsible for the thermal character of radiation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A general approach to defining thermodynamical variables in this case for spherical space-times with the Kerr-Schild metrics (1) was developed by Padmanabhan [10][11][12] who considered a canonical ensemble of space-time metrics (1) at the constant temperature of a horizon determined by the periodicity of the Euclidean time in the Euclidean continuation of the Einstein action [10]. In this approach the first law of thermodynamics for black holes described by metrics (1) is obtained in agreement with the second law as a consequence of the Einstein equations [10][11][12]. A thorough overview of the concept of honrizon is give in [56].…”
Section: Introductionmentioning
confidence: 99%
“…A year later Hawking found a quantum evaporation of a black hole [3,4] which gave the birth to thermodynamics of black holes [5][6][7] (for a review see [8]). In 1976 Gibbons and Hawking found that also cosmological horizon can radiate [9], and this gave rise to thermodynamics of horizons [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…A general approach for defining thermodynamical variables was proposed by Padmanabhan [12][13][14]. He considered the spherically symmetric Einstein equations as the thermodynamical identity for the class of solutions described by the line element (1) which leads to the results confirmed by consideration of a canonical ensemble of space-time metrics from the class (1) at the constant temperature of the horizon determined by the periodicity of the Euclidean time in the Euclidean continuation of the Einstein action; the partition function for this ensemble calculated as the path integral sum [12], can be written as…”
Section: Introductionmentioning
confidence: 99%